2020
DOI: 10.28998/rca.v18i2.7175
|View full text |Cite
|
Sign up to set email alerts
|

Sowing Dates and Molybdenum Foliar Application for Two Peanut Cultivars

Abstract: The study aimed to assess application efficiency of Mo doses through leaves in two sowing dates and different phenological stages on agronomic characteristics of two peanut cultivars. The experimental design was a randomized block with four replications, with the treatments arranged in a factorial design 2 x 2 x 6 x 2, being two cultivars (IAC Tatu and IAC 886), two sowing dates, six Mo doses applied to the leaves (0, 50, 100, 200, 400 and 800 g ha-1) and two application times (early flowering and early seed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The present findings are concordant with previous studies, where Mo supplementation increased the Mo concentration in ‘ Le-Conte ’ pear [ 37 ], grapes (cv. Merlot) [ 38 ], peanut [ 39 ] and lettuce [ 40 ]. Togay et al [ 41 ] also reported the enhanced concentration of Fe, P, Mn, Cu and Mo in lentil ( Lens culinaris Medic.)…”
Section: Discussionmentioning
confidence: 99%
“…The present findings are concordant with previous studies, where Mo supplementation increased the Mo concentration in ‘ Le-Conte ’ pear [ 37 ], grapes (cv. Merlot) [ 38 ], peanut [ 39 ] and lettuce [ 40 ]. Togay et al [ 41 ] also reported the enhanced concentration of Fe, P, Mn, Cu and Mo in lentil ( Lens culinaris Medic.)…”
Section: Discussionmentioning
confidence: 99%
“…Responses to the application of Mo in the peanut crop have been very variable in Brazil. Some studies have not reported increases in grain yield in the crop (Gericó et al., 2020; Rosolem & Caires, 1998; Soares‐Filho, Lazarini, Orioli‐Júnior, & Bernardes, 2020), although there has been a significant increase in nodulation and N uptake in peanut plants (Gericó et al., 2020). On the other hand, significant increases were obtained by Quaggio et al.…”
Section: Resultsmentioning
confidence: 99%